SUNO AI : Learning Transformation Creates Song Trough Artificial Intelligence - Fanny Andriamy; Vinna Aulya; Indrayuda Indrayuda (Komposisi: Jurnal Pendidikan Bahasa, Sastra, dan Seni, 2026)
Suno AI is being used in learning music and songwriting, and it's a good choice for helping students achieve their learning goals. Rephrase To understand how much Suno AI helps in speeding up the idea creation process for songwriting in grade 9 students at SMPN 26 Tangerang, researchers did a study. They used a qualitative method with a case study approach so they could deeply explore how Suno AI affects the creative process in music learning. Data was collected through in-depth interviews with 5 students and one music teacher. The findings showed that using Suno AI helps speed up the process of making song prototypes and changes the role of students in the creative process. Before, students were the main creators, but with Suno AI, they become creative curators. Overall, using Suno AI in learning is very helpful for achieving learning goals and helps students understand different music genres better.